Rent Seeking dan Tata Kelola Informal dalam Ekonomi Politik Bisnis Hiburan Malam di Kota Serang - Opi Sulistiya; Mahpudin Mahpudin (Catalist Indo Publisher, 2025)
This study aims to analyze rent-seeking practices and informal governance arrangements within the political economy of the nightlife business in Serang City. Although Serang is widely known as a “Santri City,” the persistence of nightlife establishments indicates a gap between formal regulatory frameworks and actual economic–political practices. This research adopts a qualitative approach using a single instrumental case study design. Data were collected through in-depth interviews and document analysis, and examined using rent-seeking theory within political economy and institutional economics. The findings reveal that rent seeking operates through institutionalized informal transactions, including concealed fees in the licensing process and informal protection provided by certain law enforcement officers and local bureaucrats. Capital-intensive nightlife entrepreneurs emerge as central actors, forming mutually beneficial relationships with members of the municipal police unit and the national police. These arrangements enable businesses to continue operating despite regulatory violations. The study concludes that rent-seeking practices have produced an informal governance system that weakens formal institutions, encourages selective law enforcement, and creates economic inefficiencies and regulatory distortions. Consequently, institutional quality deteriorates and public trust declines. Overall, the nightlife sector functions as an economic activity but as an arena of power relations shaping outcomes.